Penerapan Teknik Role Play untuk Mengembangkan Keterampilan Komunikasi Anak Usia Dini - Tama Nugroho; Arga Wijaya (Jurnal Pendidikan Bahasa dan Anak Usia Dini, 2025)
This study aims to examine the application of role play techniques in developing communication skills in early childhood. Communication is a fundamental ability that supports children's social and emotional development. This research used a qualitative descriptive method involving observations, interviews, and documentation of role play activities conducted in a kindergarten setting. The results showed that role play techniques significantly contributed to enhancing children's verbal and non-verbal communication skills. Children became more confident in expressing ideas, engaging in conversations, and understanding social cues. The role play method provided a safe and imaginative environment where children could practice communication naturally. The implications of this study suggest that educators should incorporate role play as a routine activity to stimulate the development of communication skills in early childhood education..